Prevalence of foreign body rumen impaction in slaughtered goats in Ibadan, Southwest Nigeria (2012)
A study was conducted on 4,488 goals in Ibadan, southwest sub-tropic humid zone, over a 4-month period to determine the prevalence of rumen impaction with indigestible garbage and to evaluate breed, sex and age as risk factors. Ante-mortem and post-mortem examinations were carried out on each of the animals to determine the breed, health status, sex, age and presence of indigestible garbage in the rumen. Prevalence of rumen impaction with indigestible garbage was 9.61%. It was significantly (p<0.05) higher in Red Sokoto breed than other breeds. Sex and age were found to have significant influence on the prevalence of rumen impaction. It was significantly higher (p<0.05) in females and older goats than males and younger ones, respectively.